Improving mental health care transitions through information capture during admission to inpatient mental health services: a quality improvement study - Natasha Tyler; Nicola Wright; Kyriakos Gregoriou; Justin Waring (BMC, 2021)
Abstract Background Many interventions aim to improve the transition from ward to community at the time of discharge, with varying success. Guidelines suggest that discharge planning should begin at admission, but in reality this is ideal rather than standard practice. We aimed to develop a novel information capture tool during admission that facilitates and accelerates discharge. Methods A quality improvement study to develop, implement and evaluate a novel tool that improves information capture upon admission to acute mental health wards within a single English National Health Service (NHS) trust. We developed the tool by synthesising existing evidence and working with multi-agency and multi-disciplinary professionals in two co-design workshops. During implementation the tool was piloted on three wards. Ethnographic observations (145 h) and interviews (45) were used to evaluate the implementation of the tool across the three wards. Thematic synthesis was used to consolidate the findings. Results The tool developed considerably as the process evolved. The finished product is a list of 10 information categories that should be captured from external agencies upon admission to hospital to facilitate discharge planning to community settings. Reported advantages of the tool were: (1) facilitating confidence in junior staff to legitimately question the suitability of a patient for an acute ward (2) collecting and storing essential information in a single accessible place that can be used throughout the care pathway and (3) collecting information from the services/agencies to which patients will eventually be discharged. Conclusions Improving the quality of information at admission has the potential to facilitate and accelerate discharge. The novel tool provides a framework for capturing this information that can be incorporated into existing information systems. However, the introduction of the tool exacerbated complex, fragile distributed team dynamics, highlighting the importance of sociocultural context in information flow transitional interventions within distributed teams.